2022
DOI: 10.34172/jcs.2022.07
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Anxiety in Perinatal Women

Abstract: Introduction: With a global pandemic like coronavirus disease 2019 (COVID-19) spreading across borders, creating an extensive fear amongst all groups alike due to the increased morbidity and mortality, there is uncertainty in all patients affected. The government policy of quarantine of pregnant and postnatal women with COVID-19 in hospitals leads to ironic isolation and loneliness, mounting anxiety and fear of unknown outcomes. This study was undertaken to assess maternal anxiety in relation to COVID-19 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…In some patients, this becomes a vicious cycle ruining their normal life. 18 - 20 In line with the results of the current study, horror, and stigma are directly related to each other, and labeling a patient with COVID-19 increases the patients’ anxiety and fear, which consequently weakens the patient’s immune system and makes their condition worse. 21 The results of another study showed those who are sick or quarantined may experience shame, guilt, or stigma.…”
Section: Discussionsupporting
confidence: 80%
“…In some patients, this becomes a vicious cycle ruining their normal life. 18 - 20 In line with the results of the current study, horror, and stigma are directly related to each other, and labeling a patient with COVID-19 increases the patients’ anxiety and fear, which consequently weakens the patient’s immune system and makes their condition worse. 21 The results of another study showed those who are sick or quarantined may experience shame, guilt, or stigma.…”
Section: Discussionsupporting
confidence: 80%
“…Najam R, et al in their study in India described that dysfunctional anxiety was found in 18.3% of antenatal women and 14.6% of postnatal women. This difference is due to different study settings 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Total score ranging from 1-4 signifies minimal or no depression. Mild depression is interpreted by (5-9) score, moderate depression by (10)(11)(12)(13)(14) score, moderately severe depression by (15)(16)(17)(18)(19) score and severe depression by (20)(21)(22)(23)(24)(25)(26)(27) score. In this study, depression was categorized as minimal to mild depression (PHQ-9 score <10) and moderate to severe depression (PHQ-9 score ≥ 10).…”
Section: Methodsmentioning
confidence: 99%
“…Data from the literature indicates that the pandemic has had a significant impact on maternal depression during pregnancy and in the postpartum period. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…Data from the literature indicates that the pandemic has had a significant impact on maternal depression during pregnancy and in the postpartum period. 11,12 Given that approximately 140 million babies are born every year worldwide, 13 PPD is a major public health challenge because of its importance for both maternal and child health. Anesthesiologists are concerned about short-and long-term adverse birth stressors and events in both mothers and babies.…”
Section: Introductionmentioning
confidence: 99%